In vitro Propagation of Holarrhena antidysenterica Wall., Wedelia chinensis (Osb.) Merr. and Woodfordia fruticosa (L.) Kurz. (Plant Tissue Culture and Biotechnology, 2010)
Key words:  Medicinal plant, Holarrhena antidysenterica, Wedelia chinensis,  Woodfordia fruticosa, In vitro cloning, Multiple shoot D.O.I. 10.3329/ptcb.v19i2.5443 Plant Tissue Cult. & Biotech. 19(2): 253-255, 2009 (December)    - Short communication